Spontaneous intracranial internal carotid artery dissection - Athena Mergeani; Dan Popescu; Florina Antochi (Romanian Journal of Neurology, 2010)
Spontaneous intracranial internal carotid artery dissection is an uncommon cause of cerebral infarction, particularly when compared to internal carotid artery dissection in the cervical portion. Although thromboembolism is supposed to be the main stroke mechanism in ICA dissection, haemodynamic change can also play an important role, especially in cases of intracranial dissection. We present the case of a 64-years-old female with no medical history and no signs of trauma who was admitted to our clinic for a cerebral ischemic stroke due to dissection of the left internal carotid artery in its intracranial part.